AI Agents and the Dawn of Post-Authenticity - Octavian Dumitru HERA (Eon)
This paper examines the impact of artificial intelligence (AI) agents on society, focusing on the creation of synthetic content and artificial realities. As AI agents become more advanced, the content they produce may be increasingly difficult to distinguish from human-creation, raising important ethical concerns. The study highlights how generative AI can shape perceptions and blur the boundaries between traditional, authentic content and realistic, synthetic content. It explores advancements in natural language processing and image recognition, which allow for the creation of highly convincing fake content. The paper also looks at the role of AI agents in communication and the consequent social implications. Among those implications, the paper highlights the importance of augmenting creativity rather than radically replacing it with AI agents as a tool to augment human creativity rather than replacing it. Finally, it discusses the concept of superintelligence and its potential to transform society toward post-authenticity considering balanced regulation and ethical considerations.